2015
DOI: 10.18332/tpc/60652
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Exposure to Passive Smoking among 12-18 year-old Students in Athens and Thessaloniki, Greece

Abstract: IntroductIon Passive-smoking is a major, preventable cause of disease, disability and death. It is estimated that the majority of the world's population is still living in countries not fully covered by smoke-free public health regulations and Greece is unfortunately one of them. The aim of our study, conducted in October 2014, was to provide up to date information regarding determinants of exposure to passive smoking among the student population of the two biggest Greek cities.Methods Our survey was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…26 In contrast, it was relatively lower compared with Cambodian (67.1% (95% CI: 64.0–70.0) in males and 67.4% (95% CI: 64.2–70.5) in females) 38 and Mongolian adolescents (73.9% (95% CI: 71.6–76.1) in males and 71.7% (95% CI: 69.7–73.7) in females). 39 Nonetheless, the present finding was comparable to those reported by Abidin et al 17 and Lappos et al, 40 who reported SHS exposure among 52.9% of Malaysian school children and 59.1% of adolescents aged 12–18 years in Greece, respectively. The varied proportions of SHS exposure among adolescents could be attributable to the known variation of sociodemographics, prevalence of smoking among adults and adolescents, community norm towards tobacco use and governmental legislation on smoking between different countries.…”
Section: Discussionsupporting
confidence: 90%
“…26 In contrast, it was relatively lower compared with Cambodian (67.1% (95% CI: 64.0–70.0) in males and 67.4% (95% CI: 64.2–70.5) in females) 38 and Mongolian adolescents (73.9% (95% CI: 71.6–76.1) in males and 71.7% (95% CI: 69.7–73.7) in females). 39 Nonetheless, the present finding was comparable to those reported by Abidin et al 17 and Lappos et al, 40 who reported SHS exposure among 52.9% of Malaysian school children and 59.1% of adolescents aged 12–18 years in Greece, respectively. The varied proportions of SHS exposure among adolescents could be attributable to the known variation of sociodemographics, prevalence of smoking among adults and adolescents, community norm towards tobacco use and governmental legislation on smoking between different countries.…”
Section: Discussionsupporting
confidence: 90%
“…It is evident that exposure to SHS at home and in public places in Sri Lanka remains high, despite continuous community and school based anti-smoking programmes. Similar to previous studies [ 9 12 ], the present study also reported that the presence of smokers at home was the strongest predictor of exposure to SHS both in the household and in public places. Results from this study highlight an urgent need for intervention to protect children from SHS at home.…”
Section: Discussionsupporting
confidence: 91%
“…Smoking by household members has been identified as the main predictor for SHS among children [ 9 14 ], with family groups and home environments particularly important. Allowing someone to smoke around you [ 10 ] is associated with SHS at home, with maternal smoking a stronger predictor than paternal smoking [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another Malaysian study reported a higher prevalence of 52.9% SHS exposure at home based on salivary cotinine measurement 16 . A study among Greek adolescents aged 12–18 years 22 reported 59.1% prevalence. In addition, the prevalence in this study is 15% lower than that reported in 68 low- and middle-income countries (55.9%) 23 , Cambodia (67.1%) 24 and Mongolia (73.9%, 71.6–76.1%, males; and 71.7%, 69.7–73.7% females) 25 .…”
Section: Discussionmentioning
confidence: 99%